2012
DOI: 10.1111/j.1742-7843.2012.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Paracetamol and Tropisetron on Pain: Experimental Studies and a Review of Published Data

Abstract: Experimental studies suggest that paracetamol-induced analgesia is mediated via central serotonergic pathways and attenuated by 5-HT3-antagonists. However, clinical studies do not support this, and 5-HT3-antagonists are expected to reduce pain by blocking the descending pronociceptive pathway. The current project tested whether tropisetron attenuates analgesia by paracetamol. Two randomized, double-blind, crossover studies with 18 healthy male volunteers in each were performed. Pain stimuli were cold water imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Regarding the potential target sites, it has been indicated that the synergism of nefopam and acetaminophen may occurs in connection with the descending serotonergic (5-HT) pathways and spinal serotonin 5-HT receptors. It has been reported that the potential effect of acetaminophen is indirectly/directly related to 5-HT 3 receptors at spinal sites (50,51) and descending serotonergic pathways (52). Similarly, the action of nefopam have been indicated to involve serotonergic pathways and 5-HT receptors (49,53).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the potential target sites, it has been indicated that the synergism of nefopam and acetaminophen may occurs in connection with the descending serotonergic (5-HT) pathways and spinal serotonin 5-HT receptors. It has been reported that the potential effect of acetaminophen is indirectly/directly related to 5-HT 3 receptors at spinal sites (50,51) and descending serotonergic pathways (52). Similarly, the action of nefopam have been indicated to involve serotonergic pathways and 5-HT receptors (49,53).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that acetaminophen intake for 3 days reduces the urinary excretion of PGE2 by 30% in elderly and patients with impaired renal function [25]. Other mechanisms of action of acetaminophen at a molecular level have been proposed as the production of reactive metabolites by the peroxidase function of COX-2 or interaction with serotonin receptors 5-HT3 [26,27]. The similarity in changes in cystatin C and creatinine values throughout the study in patients treated with dipyrone and acetaminophen supports the idea that dipyrone used for short periods of time might be safe in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Controversial data have been observed between the results in healthy volunteers and patients with pain. 16 The findings of these studies will be discussed in the following sections.…”
Section: The Role Of the Central Serotonergic System In Acetaminophenmentioning
confidence: 98%